Chemical properties of key metabolites determine the global distribution of lichens. (16th November 2021) - Schweiger, Andreas H.; Ullmann, G. Matthias; Nürk, Nicolai M.; Triebel, Dagmar; Schobert, Rainer; Rambold, Gerhard
Abstract: In lichen symbioses, fungal secondary metabolites provide UV protection on which lichen algae such as trebouxiophycean green algae—the most prominent group of photobionts in lichen symbioses—sensitively depend. These metabolites differ in their UV absorbance capability and solvability, and thus vary in their propensity of being leached from the lichen body in humid and warm environments, with still unknown implications for the global distribution of lichens. In this study covering more than 10, 000 lichenised fungal species, we show that the occurrence of fungal‐derived metabolites in combination with their UV absorbance capability and their probability of being leached in warm and humid environments are important eco‐evolutionary drivers of global lichen distribution. Fungal‐derived UV protection seems to represent an indirect environmental adaptation in which the lichen fungus invests to protect the trebouxiophycean photobiont from high UV radiation in warm and humid climates and, by doing this, secures its carbon source. Abstract : In lichen symbioses, secondary metabolites produced by the lichen fungi (mycobionts) provide UV protection on which trebouxioid green algae as the most prominent photobionts sensitively depend. These metabolites differ in their UV absorbance capability and solvability and therefore vary in their propensity of being leached from the lichen body by high precipitation and temperatures with still unknown implications for the global distribution of lichens. In this global study, we show that the occurrence and chemical properties of these metabolites are of eco‐evolutionary importance for the global, latitudinal distribution of lichenised trebouxioid green algae. This close eco‐evolutionary link between lichen chemistry and distribution might represent an indirect environmental adaptation in which the mycobiont invests to protect the trebouxioid photobiont from harsh environmental conditions (i.e. high UV radiation) and, thereby safeguards its efficient source of photosynthetic carbon.